2023
DOI: 10.1007/s00701-023-05581-y
|View full text |Cite
|
Sign up to set email alerts
|

Multi-layered repair of high-flow CSF fistulae following endoscopic skull base surgery without nasal packing or lumbar drains: technical refinements to optimise outcome

Abstract: Aims Post-operative CSF leak remains a significant problem following endoscopic skull base surgery, particularly when there is a high-flow intra-operative CSF leak. Most skull base repair techniques are accompanied by the insertion of a lumbar drain and/or the use of nasal packing which have significant shortcomings. Our aim was to review the results of a large series of endoscopic skull base cases where a high-flow intra-operative CSF leak rate was encountered and repaired to assess if modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…The introduction of the vascularised nasoseptal flap (NSF), pedicled on the sphenopalatine artery, was transformative in the reduction of the incidence of post-operative CSF leak following EEA, which were in excess of 30% in early series ( 40 , 42 , 43 ). In the intervening period following the introduction of the NSF further adjuncts to skull base repair following EEA have been advocated, including the use of tissue sealants, multiple layers of autologous fascia lata, autologous fat graft and nasal packing, although none have demonstrated such a dramatic impact on the rate of post-operative CSF leak as the use of the NSF ( 44 46 ). In an effort to further reduce the incidence of post-operative CSF leak, the use of prophylactic lumbar drainage has been advocated: a single centre randomised controlled trial (RCT) of post-operative lumbar drainage demonstrated a significant reduction in the rate of post-operative CSF leak when compared to the cohort randomised to no prophylactic lumbar drainage (8% vs 21%) ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of the vascularised nasoseptal flap (NSF), pedicled on the sphenopalatine artery, was transformative in the reduction of the incidence of post-operative CSF leak following EEA, which were in excess of 30% in early series ( 40 , 42 , 43 ). In the intervening period following the introduction of the NSF further adjuncts to skull base repair following EEA have been advocated, including the use of tissue sealants, multiple layers of autologous fascia lata, autologous fat graft and nasal packing, although none have demonstrated such a dramatic impact on the rate of post-operative CSF leak as the use of the NSF ( 44 46 ). In an effort to further reduce the incidence of post-operative CSF leak, the use of prophylactic lumbar drainage has been advocated: a single centre randomised controlled trial (RCT) of post-operative lumbar drainage demonstrated a significant reduction in the rate of post-operative CSF leak when compared to the cohort randomised to no prophylactic lumbar drainage (8% vs 21%) ( 7 ).…”
Section: Discussionmentioning
confidence: 99%